Interleukin-2 drives cortisol secretion in an age-, dose-, and body composition-dependent way - Roelfsema, Ferdinand (Endocr Connect, 2020)
BACKGROUND: Interleukin-2 (IL-2), one of the proinflammatory cytokines, is used in the treatment of certain malignancies. In some studies, transient increases in cortisol and ACTH secretion occurred. Thus, this agent may be used as an experimental probe of adrenal cortisol secretion. OBJECTIVE: This study quantifies the effects of low and moderate doses of IL-2 on cortisol secretion and assesses the modulation by age, dose and body composition. SITE: Mayo Clinical Translational Research Unit. SUBJECTS: Study comprised 35 healthy men, 17 young and 18 older. METHODS: Randomized prospective double-blind saline-controlled study of IL-2 administration in two doses with concurrent 10-min blood sampling for 24 h. OUTCOME MEASURES: Deconvolution analysis and approximate entropy of cortisol secretion. RESULTS: Low-dose IL-2 administration increased nocturnal pulsatile cortisol secretion from 1460 ± 160 to 2120 ± 220 nmol/L/8 h in young subjects and from 1680 ± 105 to 1960 ± 125 nmol/L/8 h (treatment P < 0.0001, but more in young than older, P = 0.02). Comparable results were obtained for total cortisol secretion (P treatment <0.0001, age effect P = 0.005). The higher IL-2 dose caused a large increase in young (P < 0.0001), but not in older (P = 0.90) subjects. This dose also increased approximate entropy from 0.877 ± 0.041 to 1.024 ± 0.049 (P = 0.008), pointing to reduced secretory orderliness. Incremental cortisol (nocturnal) secretion correlated negatively with visceral fat mass (R = −0.41, P = 0.019). CONCLUSION: In healthy men, IL-2 injection drives pulsatile cortisol secretion in a dose-dependent way in young, but not older, individuals and erodes cortisol secretory orderliness at a higher dose in young subjects. Cortisol responses are diminished with increasing abdominal visceral fat mass.